Extrinsic Motives And Impact Of Using Chat GPT As A Learning Resource On Midwifery Students Of STIKES Panrita Husada, Bulukumba - Asmirati; Mitra Asriani Amin (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2026)
Technology is a key element in implementing digital learning across various media, applications, and devices. The use of technology opens up opportunities for digital learning that is boundless in space and time, enabling access anytime and anywhere (Marlya Fatria 2021). One technological innovation in this modern era is chatGPT (Andre Mustofa Meihan et al., 2023). This technology is the result of artificial intelligence innovation that provides a fresh and modern learning experience for both students and university students. The purpose of this study was to determine the extrinsic motives and the impact of using chatGPT as a learning resource on Midwifery students at the Panrita Husada Bulukumba Health College. The results of this study can serve as a foundation for increasing scientific insight in utilizing chatGPT as a learning resource and can help students better understand the impact of technology use, especially artificial intelligence such as chatGPT, in the context of education and learning. This research can also be a basis for teachers to be able to know the motives of Midwifery students of Stikes Panrita Husada Bulukumba who use chatGPT and its impacts. As well as adding references for researchers in developing knowledge and insight into the use of chatGPT as a learning resource in the digital era. This research was conducted at the Stikes Panrita Husada Bulukumba campus, Jl.Pendidikan Taccorong, Gantarang District, Bulukumba Regency. The selection of the place was adjusted to the selection of the population and sample, namely Midwifery students of Stikes Panrita Husada Bulukumba and was carried out from August - October 2025 with a quantitative research method and using a Phenomenological approach that examines human experience. The results of this study found intrinsic and intrinsic motivation of students, namely the desire to succeed, the challenges of the work itself, and the encouragement to support learning activities, as well as environmental conditions and social relationships as extrinsic motivation. The use of chat GPT also has negative and positive impacts for individual users.